1997
DOI: 10.1046/j.1464-410x.1997.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative blood loss after transurethral prostatectomy is dependent on in situ fibrinolysis

Abstract: Objective To evaluate whether post-operative blood lossResults The post-operative blood loss correlated significantly with the per-operative loss (P=0.047) and the in patients with benign prostatic hyperplasia, undergoing transurethral resection of the prostate (TURP), weight of resected tissue (P=0.029). There was a highly significant correlation between the area under depends on in situ fibrinolysis in urine, and to determine the relative contributions of the urokinase and the curve of FbDP in the urine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…Although the most likely mechanism for bleeding is the effect on platelet function it is noteworthy that ASA not only acetylates cyclooxygenase but also fibrinogen (14), and this may lead to alteration in the fibrin structure making it more susceptible to lysis by plasminogen activators (15). If this is the case, it is in accordance with our previous study where we demonstrated that the postoperative blood loss after TURP was dependent on in situ fibrinolysis (16).…”
Section: Discussionsupporting
confidence: 89%
“…Although the most likely mechanism for bleeding is the effect on platelet function it is noteworthy that ASA not only acetylates cyclooxygenase but also fibrinogen (14), and this may lead to alteration in the fibrin structure making it more susceptible to lysis by plasminogen activators (15). If this is the case, it is in accordance with our previous study where we demonstrated that the postoperative blood loss after TURP was dependent on in situ fibrinolysis (16).…”
Section: Discussionsupporting
confidence: 89%
“…We believe the prolonged course of urethral bleeding was likely due to a deficiency of vWF and the presence of naturally occurring fibrinolytic substances in urine [16,17]. One occurred following Foley catheterization and the other was spontaneous.…”
Section: Discussionmentioning
confidence: 91%
“…the liver, spleen and kidney Colonic polyp resection, where bleeding may occur at the transected stalk (Sorbi et al , ) Bowel resection in which bleeding may occur at the bowel anastomosis site Cardiac, intracranial or spinal surgery, where a bleed can have significant consequences (Lazio & Simard, ; Jones et al , ; Mangano, ) Pacemaker or implantable cardioverter – defibrillator device implantation, where the risk of haematoma development is significant (Jamula et al , ; Robinson et al , ; Tischenko et al , ; Chow et al , ). However, recent results from the BRUISE CONTROL study demonstrated that continuing oral VKA therapy is superior to using UFH or LMWH, in the context of pocket haematoma formation (Birnie et al , ) Procedures associated with the urogenital tract, where endogenous urokinase is thought to promote bleeding (Watson et al , ; Nielsen et al , ; Ihezue et al , ). Such procedures include transurethral prostate resection, bladder resection or tumour ablation, nephrectomy and kidney biopsy…”
Section: Procedures That May Require Bridging Therapy To Be Prescribedmentioning
confidence: 99%